23 fractional factorial design for polymer based thin film composite (TFC) membrane synthesis for CO2/CH4 separation - Alia Aqilah, Ghazali; Raj Krishna Roshan, Kanasan; Sunarti, Abd Rahman; Mohamad Syafiq, Abdul Wahab; Nadia Sofea, Hazleen; Norhidayana, Mandayar (IOP Publishing, 2019)
Membrane technology is dominating the industry as an attractive approach for biogas purification due to its outstanding performance. Recently, there have been intensive efforts in the development of better separation efficiency of membrane which include altering the materials and modifying the methods in preparing the membrane. A well-formed membrane is when they achieved both high permeability and excellent separation ability. Therefore, this study is focusing on identifying the best processing factors in PVC/Pebax thin film composite (TFC) membrane development towards CO2/CH4 separation by employing 23 fractional factorial design (FFD). A total of three factors; immersion times (5 & 15 min), Pebax concentration (1 & 5 wt%) and number of coating layers (1 & 4) were chosen to run simultaneously with CO2 permeability and ideal selectivity as the responses for this study. The results show that the most influential factors that affect the permeability are immersion time and Pebax concentration, while for selectivity are Pebax concentration and number of coating layer. The best condition was known to maximize the permeability and selectivity. The identified conditions were immersion time for 15 min, Pebax concentration at 5wt% and 4 layers of coating which gave CO2 permeability and gas selectivity of 19612 Barrer and 7.15, respectively. The outcome of this study indicates that FFD was suitable to minimize and eliminate factors by considering the interaction among the factors involves in membrane film synthesis for excellent gas separation performance. Besides, the existence of Pebax layer was verified by visual interpretation using Scanning electron microscopy (SEM) and Fourier Transform Infrared (FTIR).